Impact of COVID-19 pandemic on diagnostic pathology in the Netherlands - M. L. F. van Velthuysen; S. van Eeden; S. le Cessie; M. de Boer; H. van Boven; B. M. Koomen; F. Roozekrans; J. Bart; W. Timens; Q. J. M. Voorham (BMC, 2022)
Abstract Background The COVID-19 pandemic has a huge impact on healthcare provided. The nationwide pathology registry of the Netherlands, PALGA, offers an outstanding opportunity to measure this impact for diseases in which pathology examinations are involved. Methods Pathology specimen numbers in 2020 were compared with specimen numbers in 2019 for 5 periods of 4 weeks, representing two lockdowns and the periods in between, taking into account localization, procedure and benign versus malignant diagnosis. Results The largest decrease was seen during the first lockdown (spring 2020), when numbers of pathology reports declined up to 88% and almost all specimen types were affected. Afterwards each specimen type showed its own dynamics with a decrease during the second lockdown for some, while for others numbers remained relatively low during the whole year. Generally, for most tissue types resections, cytology and malignant diagnoses showed less decrease than biopsies and benign diagnoses. A significant but small catch-up (up to 17%) was seen for benign cervical cytology, benign resections of the lower gastro-intestinal tract, malignant skin resections and gallbladder resections. Conclusion The COVID-19 pandemic has had a significant effect on pathology diagnostics in 2020. This effect was most pronounced during the first lockdown, diverse for different anatomical sites and for cytology compared with histology. The data presented here can help to assess the consequences on (public) health and provide a starting point in the discussion on how to make the best choices in times of scarce healthcare resources, considering the impact of both benign and malignant disease on quality of life.